Obstetrical vacuum extraction practice in Senegal: knowledge, attitude and practices - Mbaye, Magatte; Gueye, Mamour; Diaboula, Sountou; Gueye, Mame Diarra Ndiaye; Diouf, Aliou; Wade, Mouhamadou; Saheli, Brahem; Abdoulaye, Mihimit; Moreau, Jean Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background:Assess knowledge, attitudes and practices of healthcare providers in the three biggest regions in Senegal, appreciate their level of training and determine the frequency of the practice of vacuum extraction in health facilities. Methods: This was a prospective study conducted over 1 year from January 1 to December 31, 2015 with a survey through interviews using a semi-structured questionnaire with open or closed questions, single or multiple-choice. Were included in the study providers practicing vacuum extractor, officiating in Dakar, Thies and Saint-Louis in the private and/or public sector who agreed to participate in the study. Data were captured and analyzed using File Maker Pro version 12 Inc*, then SPSS (Statistical Package for Social Science) version 21.0. Results: Out of 250 healthcare providers, 223 accepted to answer the questionnaire leading to an acceptance rate of 89.2%. 142 healthcare providers (63.7%) were trained in vacuum extraction. A proportion of 62.3% of providers knew the indications of vacuum extraction. For contraindications, only 34.5% of providers were able to cite one of them. Complications of vacuum extraction were known to 58.7% of our providers. There was a statistically significant difference between doctors and the others (midwifes, nurses) in the knowledge of indications, contraindications and complications of vacuum extraction. The only discriminatory parameter leading to this difference was initial and continuous training in vacuum extraction. Conclusions: It is important to introduce obstetric vacuum training in the gynaecology and obstetrics program for medical students and midwifery training schools, reinforce this training using simulators, include the practice of vacuum extraction in the internship objectives of medical students and midwives and evaluate them regularly.